Knowledge, Attitude and Practices Adopted by Recreational Runners Towards Core Stability Exercises in Preventing Low Back Pain: A Cross-Sectional Study - Vinosh Kumar Purushothaman; Ivan Ho Heng Kit; Ambusam Subramaniam; Arun Vijay Subbarayalu; Sivasankar Prabaharan; Palanivel Rubavathi Marimuthu; Everlynn Yi Xuan Hii; Sivakumar Chinnusamy; Mohanraj Kandasamy (OVS LLC, 2023)
The current study intended to determine recreational runners' knowledge, attitude, and practices toward CSE to prevent LBP. Materials and Methods: A cross-sectional study design was adopted. Two hundred fifty-seven recreational runners were chosen using a simple random sampling approach and administered with a semi-structured questionnaire to evaluate their KAP toward CSE. Data analysis was carried out using SPSS 28.0. Results:  The correct response to the knowledge-related items in the questionnaire was from 65% to 91%. Precisely, 91.4% of study participants understood CSE. Furthermore, most participants showed a positive attitude toward CSE, considering that it is essential for running (79%), improving fitness (76%), reducing the risk of injuries (71%), and boosting their appearance (54%). Most participants (>85%) performed CSE for recommended frequency and duration to strengthen their core muscles and prevent LBP. The recreational runners had good practice toward CSE. Conclusion:  Recreational runners possess adequate knowledge, a positive attitude, and good practice toward CSE. This study suggested that motivational strategies and awareness programs can be conducted to improve recreational runners' KAP toward CSE preventing LBP.